Clinical characteristics of Treponema denticola-associated lung abscess diagnosed by metagenomic next-generation sequencing: a case series analysis - Xu, Hangdi; Xu, Yueqing; Gu, Jing; Wang, Xiaoling; Liao, Bo; Zhou, Pengpeng; Wu, Shengjun; Tao, Ran; Fu, Ying (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionTreponema denticola is an oral anaerobic bacterium commonly associated with periodontitis, but its role in lower respiratory tract infections (e.g., lung abscess) has long been overlooked. For bacteria that grow anaerobically, traditional culture methods exhibit low detection rates, which directly lead to the mis-diagnosis of anaerobic infection. With the ultilization of metagenomic next-generation sequencing (mNGS) in clinical practice, we studied the clinical features and treatment strategies of T. denticola-associated lung abscess.MethodsA retrospective analysis was conducted on patients confirmed with T. denticola lung abscess by mNGS from October 2023 to October 2024. Routine aerobic bacterial culture and stains were used. Histopathological analysis and Warthin-Starry silver staining was completed on samples from lung tissue. A literature review was performed using PubMed and CNKI (up to June 2025).ResultsSeven patients were diagnosed with T. denticola lung abscess under mNGS. The cohort predominantly comprised elderly males (mean age 62.3 years), all of whom had underlying oral diseases. Clinical manifestations featured chronic cough (mean symptom duration 3.6 months) and frequent hemoptysis (85.7%), with notably mild systemic inflammation (only one febrile case). Characteristic CT findings included mass-like lesions with necrosis (100%) and cavitation (71.4%), without air-fluid levels. Conventional cultures were overwhelmingly negative, whereas mNGS detected T. denticola in all seven cases. Among the seven patients, one showed clinical improvement after two months of amoxicillin-clavulanate therapy, and another responded well to seven months of doxycycline treatment. The remaining five patients initially treated with levofloxacin or moxifloxacin demonstrated poor responses, with three cases ultimately requiring surgical resection of the lesions.DiscussionT. denticola lung abscess is most commonly seen in individuals with poor oral hygiene. It presents as an indolent, chronic course and a high incidence of hemoptysis. Typical CT findings include a mass-like lesion with cavitation but no air–fluid level. Traditional microbiological detection often yield false negative results, making mNGS a critical diagnostic tool. First-line therapy should include β-lactams or tetracyclines, and surgery is warranted for refractory cases or massive hemoptysis.